E-Commerce in Small and Medium Enterprises (SMEs) in order to Improve Performance - Andi Hendrawan; Hari Sucahyowati; Kristian Cahyandi (STKIP Singkawang, 2018)
The role of SMEs in the economy of a country, including Indonesia, cannot be underestimated. For example, in the Netherlands, SMEs constitute 98.8% of existing companies and absorb 55% of the workforce. A total of 35 million US dollars of Italian exports is the contribution of SMEs that absorb 2.2 million workers. In Vietnam, 64% of the workforce is absorbed by SMEs. The same thing happened in Indonesia. One application of ICT and the internet in the field of business and trade is electronic commerce (e-commerce). The purpose of the study was to determine the effect of e-commerce on improving the performance of SMEs. Sample to be studied is Small Business Medium in Cilacap, Indonesia. This study uses quota sampling that will be taken a sample of 30 units of SMEs. The sampling technique used is purposive sampling Analyzed performance difference is the performance of SMEs in the show with two dimensions of the increasing number of sales and number of relations, Analysis using statistical program package. Based on the results of the research can be concluded that e-commerce has a positive effect on performance SMEs. This is shown by the increasing sales and relationships of SMEs. More sales will increase the income that the end is the welfare of SMEs.